2007
DOI: 10.1038/sj.eye.6702992
|View full text |Cite
|
Sign up to set email alerts
|

Pseudoexfoliation syndrome prevalence in Greek patients with cataract and its association to glaucoma and coronary artery disease

Abstract: Purpose To investigate the prevalence of glaucoma and coronary artery disease (CAD) in patients with cataract and pseudoexfoliation (PEX) syndrome. Methods Cross-sectional study of 2140 consecutive patients with cataract admitted at the University Hospital of Patras, Greece, for cataract surgery. Only patients with senile cataract were included in this study. All patients underwent a complete ophthalmological examination that included slit-lamp evaluation with dilated pupil for PEX material in the anterior seg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
63
2
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(85 citation statements)
references
References 42 publications
10
63
2
4
Order By: Relevance
“…[4][5][6][7][8][9][10][11][12][13][14][15][16][17] In studies done in other places, the prevalence of PXS has been increased with age increasing that has been in line with the results of present study. [4][5][6]9,10,[12][13]15,17 Different results obtained in previous studies in terms of the difference between the two sexes which sex difference has not been observed in some studies (Morano Montane study in Spain, Arvind H study in southern India, Susic N study in Croatia, but in some studies in line with this study, the disease is more common in women than in men (63/9% of men and 36/1% in women) which probably shows the different disease behaviors in present region and perhaps some other regions of the world.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…[4][5][6][7][8][9][10][11][12][13][14][15][16][17] In studies done in other places, the prevalence of PXS has been increased with age increasing that has been in line with the results of present study. [4][5][6]9,10,[12][13]15,17 Different results obtained in previous studies in terms of the difference between the two sexes which sex difference has not been observed in some studies (Morano Montane study in Spain, Arvind H study in southern India, Susic N study in Croatia, but in some studies in line with this study, the disease is more common in women than in men (63/9% of men and 36/1% in women) which probably shows the different disease behaviors in present region and perhaps some other regions of the world.…”
Section: Discussionsupporting
confidence: 81%
“…In terms of developing glaucoma or elevated intraocular pressure similar to previous studies significant differences between the two groups were observed (2 eyes in the control group and 43 eyes in the case group) that this difference is meaningful and this indicates that the presence of PXS is an important risk factor for glaucoma or elevated intraocular pressure. 5,7,9,[12][13][14][15][16][17][18] In terms of C / D ratio above 5/10, the increase in the case group is significant (P=0.021), which indicates a lack of proper screening of patients or lack of referring the patients to measure intraocular pressure and the correct follow up and considering that in case of loss of optic nerve disease (high ratio C / D) , glaucoma is not returnable, so planning and designing of health authorities to screen at risk people, especially in elderly, and in case of the presence PXS, is absolutely necessary.…”
Section: Discussionmentioning
confidence: 99%
“…7,[22][23][24] In a previous study, PEX was found to be positively associated with the risk for cardiovascular diseases among patients with age Z50, and PEX was suggested as a risk factor for cardiovascular diseases. 25 To our best knowledge, we are the first to show the elevated serum YKL-40 levels, a new potential biomarker of inflammation and vascular dysfunction, in patients with PEX. In our study, PEX group had also elevated systolic and diastolic blood pressures, serum HsCRP, total cholesterol, LDL, and triglycerides levels, and reduced serum HDL levels, which were predictors for cardiovascular diseases.…”
Section: Resultsmentioning
confidence: 99%
“…[7][8][9][10][11][12] Exfoliation material (XFM) is found not only in ocular tissues, [13][14][15] and several systemic disorders have been associated with XFS, such as peripheral vascular occlusions, increased carotid stiffness, coronary artery disease, stroke, Alzheimer's disease, and hearing loss. [16][17][18][19][20][21][22][23] The pathogeneses and clinical features of acute retinal vascular occlusions (RVOs) are still not well understood. 24,25 Central retinal vein occlusion (CRVO) has been described in eyes with XFS, even when exfoliative glaucoma (XFG, a known risk factor) was not present.…”
Section: Introductionmentioning
confidence: 99%